Design and analysis of a biogas production system utilizing residual energy for a hybrid CSP and biogas power plant. (25th October 2016) - Zhang, G.; Li, Y.; Dai, Y.J.; Wang, R.Z.
Highlights: The volume of anaerobic digester increases with the increase of HRT. Hybridizing solar energy with biogas energy improves the power stability. The increase of SPSR can obviously improve the electricity generation. The higher the onset of feedstock costs, the larger the economic potential. Abstract: This paper proposes a novel hybrid CSP and biogas power plant in which biogas is produced with anaerobic treatment of liquid cattle manure under mesophilic conditions. The residual energy from the hybrid power plant is used to maintain the digester content at the optimum temperature of 35 °C for stable production of biogas. A simulation model for the power plant with focus on the biogas production has been developed on TRNSYS platform. The thermal performance and dynamic behaviors of this biogas production system under typical climatic conditions in West China are investigated. It is found that the volume of anaerobic digester increases with the increase of hydraulic retention time while the feedstock flow rate decreases with the increase of hydraulic retention time. The maximum temperature fluctuation of the digester in a day is less than 0.8 °C with PID control, which guarantees the yield and quality of biogas. For the hybrid power plant, hybridizing solar energy with biogas energy not only improves the power stability but also increases power dispatchability. The increase of solar power sharing ratio can obviously improve the total electricity generation of the hybrid power plant without obvious negative impact on the total efficiency of the hybrid power plant.